Gambaran Peran Kesiapsiagaan BEM dan Mahasiswa dalam Penanggulangan Bencana - Riyad Rahmatillah; Hikmat Pramajati; Rafika Rosyda (Universitas Negeri Gorontalo, 2025)
This research is motivated by the importance of disaster preparedness in higher education settings, particularly concerning the role of student organizations and the preparedness level of students. The study aims to describe the preparedness roles of the Student Executive Board (BEM) and students of UPI Sumedang in disaster management. A mixed-method approach was used, consisting of document analysis to assess the completeness of BEM archives from 2020–2024 and a descriptive quantitative survey involving 307 students to evaluate preparedness based on four parameters. The findings show that student preparedness falls into the “ready” category, with the highest proportion at the “very ready” level in the aspects of knowledge, emergency response planning, early warning systems, and resource mobilization. However, the document review indicates that BEM’s archival completeness remains limited, with only 34 out of 70 documents meeting the preparedness role indicators. No documents were found related to policies, strategies, or monitoring and evaluation, indicating weaknesses in the organization’s long-term planning. In conclusion, student preparedness is relatively strong, but it is not yet fully supported by BEM’s institutional capacity, highlighting the need for strengthened policies, coordination, and documentation to support the campus disaster management system.